Fractional molecular charge studied via molecular vibrational properties: specific aspects in Jahn-Teller active molecular species - Bâldea, Ioan (RSC Advances, 2016)
In this paper, we report results obtained within the density functional theory (DFT) demonstrating that information on the fractional (non-integral) charge of a single molecule can be extracted from its vibrational properties. This is important because, unlike the former, the latter can be measured experimentally, e.g., via surface enhanced Raman spectroscopy (SERS). As a concrete example, we choose a benzene molecule and consider changes brought about by continuously varying the fractional charge from q = 0 to q = 1 corresponding to neutral and radical cation species. Molecular electronics or electrochemical platforms may offer experimental realizations of continuously tuning non-integral molecular charges. We found that changes in the vibrational frequencies ωv(q) can be substantially larger than those recently measured by varying applied bias in molecular junctions. Our results indicate important qualitative and quantitative differences between the dependence ωv = ωv(q) exhibited by vibrational modes that are JT active and those that are JT inactive; typically, the former is stronger and nonlinear, while the latter is weaker and linear.